POVERTY, INEQUALITY AND NATIONAL HEALTH INSURANCE SCHEME: RECONSTRUCTING THE RIGHT TO HEALTH IN NIGERIA - Olanrewaju, Oluwaseun; Marcus, Babatola Adeleye; Oni, Joseph Abidemi (EBSU Journal of Social Sciences and Humanities, 2023)
The National Health Insurance Scheme (NHIS) was established in Nigeria to provide accessible and affordable healthcare to the citizens. However, the inherent weaknesses and poor implementation of the NHIS Act hampered the objectives which the scheme sought to achieve. There is glaring evidence that citizens living in poverty, lack access to healthcare services. This brings to the fore the commitment of the government towards protecting the right to health in Nigeria. Sadly, the right to health is not stated as a Fundamental Human Right (FHR) in the 1999 Constitution of Nigeria. In 2022, the government passed the National Health Insurance Authority (NHIA) Act. The Act which came into effect on 19 May 2022 repeals the NHIS Act, 2004. However, the implementation of the NHIA Act is slow. Consequently, analyzing the NHIS Act, and the complexities that militated against its effective implementation still hold much relevance. The paper utilizes secondary sources of data derived from journal articles, newspaper publications, institutional websites, books and policy documents. Furthermore, it adopts vulnerability theory as its theoretical framework. It emphasizes that beyond enacting a national health insurance law, the right to health must importantly be recognized and implemented as a fundamental human right. The paper concludes that in order for the NHIA Act to be fully implemented, the right to health must be recognized as a justiciable right in the Nigerian legal jurisprudence. Significantly, Civil Society Organizations (CSOs) and Non-Governmental Organizations (NGOs) must provoke legislative advancement towards the reworking of the constitution in this regard.